2016
DOI: 10.1073/pnas.1524013113
|View full text |Cite
|
Sign up to set email alerts
|

KCC2 rescues functional deficits in human neurons derived from patients with Rett syndrome

Abstract: Rett syndrome is a severe form of autism spectrum disorder, mainly caused by mutations of a single gene methyl CpG binding protein 2 (MeCP2) on the X chromosome. Patients with Rett syndrome exhibit a period of normal development followed by regression of brain function and the emergence of autistic behaviors. However, the mechanism behind the delayed onset of symptoms is largely unknown. Here we demonstrate that neuron-specific K+-Cl− cotransporter2 (KCC2) is a critical downstream gene target of MeCP2. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
183
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(189 citation statements)
references
References 59 publications
6
183
0
Order By: Relevance
“…Although the actual mechanisms that control the developmental expression of chloride cotransporters are not clear, MeCP2 is known to regulate neuronal activity-dependent expression of BDNF (27), which promotes the developmental up-regulation of KCC2 (89) and the maturation of cortical inhibition (88). Overexpression of KCC2 in MeCP2-deficient human neurons differentiated from induced pluripotent stem cells from patients with RTT has recently been shown to rescue GABA functional deficits (90). Neuronal Cl − regulation through KCC2 thus offers an attractive target for postsynaptic modulation of inhibition in RTT.…”
Section: Discussionmentioning
confidence: 99%
“…Although the actual mechanisms that control the developmental expression of chloride cotransporters are not clear, MeCP2 is known to regulate neuronal activity-dependent expression of BDNF (27), which promotes the developmental up-regulation of KCC2 (89) and the maturation of cortical inhibition (88). Overexpression of KCC2 in MeCP2-deficient human neurons differentiated from induced pluripotent stem cells from patients with RTT has recently been shown to rescue GABA functional deficits (90). Neuronal Cl − regulation through KCC2 thus offers an attractive target for postsynaptic modulation of inhibition in RTT.…”
Section: Discussionmentioning
confidence: 99%
“…KCC2 maintains low [Cl - ] i in mature neurons, which is essential for maintaining proper postsynaptic inhibition mediated by GABA A receptors (GABA A Rs) and glycine receptors (GlyRs) (Braat and Kooy, 2015a; Kaila et al, 2014; Rivera et al, 1999). Impaired KCC2 activity and subsequent increases in [Cl - ] i occur in several neurological disorders (Boulenguez et al, 2010; Coull et al, 2003; Tang et al, 2016), leading to a depolarizing action of GABA A R mediated currents due to a positive shift of E GABA , and over-excitation of neuronal network activity (Ben-Ari, 2002; Ben-Ari et al, 2012; Blaesse et al, 2009). Recent experiments on KCC2 processing suggest that the intrinsic ion transport rate, cell surface stability, and trafficking of plasmalemmal KCC2 are rapidly and reversibly modulated by the (de)phosphorylation of critical serine and tyrosine residues at the C-terminus of this protein (Lee et al, 2010, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Djuric et al 86 , went on to also show that RTT neurons had decreased cell capacitance, dysfunction in action potential generation, dysfunction in voltage-gated sodium currents, and dysfunction in miniature excitatory synaptic current frequency and amplitude. Two studies demonstrated particularly well the power of hiPSCs by showing that RTT neurons had a delayed functional switch in GABA from excitatory to inhibitory 84 and neuronal progenitors from RTT patients had an increased frequency of L1 retrotranspositions 83 , conclusions almost impossible to derive from any other experimental medium. Tang et al went on further to show that IGF1 treatment rescued GABA functional deficits 84 .…”
Section: Induced-pluripotent Stem Cell Models Of Neurodevelopmentamentioning
confidence: 99%
“…Two studies demonstrated particularly well the power of hiPSCs by showing that RTT neurons had a delayed functional switch in GABA from excitatory to inhibitory 84 and neuronal progenitors from RTT patients had an increased frequency of L1 retrotranspositions 83 , conclusions almost impossible to derive from any other experimental medium. Tang et al went on further to show that IGF1 treatment rescued GABA functional deficits 84 . In addition, Rett gain of function by gene duplication (MECP2dup) has also been modeled in hiPSC lines, showing a phenotype in many respect opposite to that of Rett loss of function, namely increased synaptogenesis and dendritic complexity along with altered neuronal network synchrony 73 .…”
Section: Induced-pluripotent Stem Cell Models Of Neurodevelopmentamentioning
confidence: 99%